Silent spread of mcr-9 in ESBL-producing Enterobacteriaceae clinical isolates, Jimma, Ethiopia - Sewunet, Tsegaye; Razavi, Mohammad; Tellapragada, Chaitanya; Giske, Christian G. (PloS one, 2025)
Mobile colistin resistance (MCR) genes, have been increasingly identified worldwide, but their presence and characteristics in Africa remain poorly understood. Herein, we characterized a silent mcr-9 gene carried in Enterobacteriaceae from Ethiopia. In a study investigating genomic epidemiology of ESBL-producing Gram-negative bacilli from clinical samples in 2016, eleven isolates were found to encode mcr-9 genes. Whole genome sequencing, combining Illumina and MinION Nanopore technologies were performed for in-depth investigation of the genome and understand the genetic contexts of mcr-9 and its associated plasmids. The mcr-9 genes were detected in Enterobacter cloacae (n = 8), Escherichia coli (n = 1), Klebsiella pneumoniae (n = 1), and K. michiganensis (n = 1). They were isolated from urine (54.5%, 6/11), wound secretions (27.3%, 3/11), and fecal samples (n = 18.2%, 2/11). In addition to mcr-9, all isolates encoded blaCTX-M-15, and aac (6')-Ib-cr among several other resistance genes. These isolates were susceptible to colistin (MIC ≤ 0.5 mg/L). The E. cloacae strains belong to three different sequence types (ST): ST114 (n = 3), ST184 (n = 3), ST254 (n = 1), and Enterobacter mori ST2197 (n = 1)), whereas the E. coli and the K. pneumoniae strains belonged to ST410 and ST337. IncHI2 and IncHI2A plasmid replicons were present in all isolates. Although the genetic content of plasmids carrying the mcr-9 genes varied, the genetic contexts surrounding all mcr genes within ±10kb region were largely consistent, mostly flanked by composite transposons such as IS26, and IS903B. A silent mcr-9 gene was detected among ESBL-producing Enterobacteriaceae isolates. The IncHI2 plasmids encoding the mcr-9 had 25% genetic content dissimilarity.